MODERN PROBLEMS OF MEDICAL AND PHARMACEUTICAL CARE FOR OCCUPATIONAL DISEASES - Андрей Георгиевич Петров; Виктор Андреевич Семенихин; Ольга Владимировна Хорошилова; Сергей Николаевич Филимонов; Наталья Степановна Черных (Medicina v Kuzbasse, 2022)
Comprehensive medical and pharmaceutical studies of the problem of occupational morbidity in Kuzbass were not carried out enough, while the results obtained will contribute to solving the problem of occupational diseases (OD), maintaining the health of the working population.